The Quality of Regulations About Criminal Liability for the Crimes Which Create Conditions for Illegal Consumption of Drugs - Arsenii A. Bimbinov (Сибирское юридическое обозрение, 2017)
The article is dedicated to the research of statutorisation of criminal liability for actions which cause conditions of unlawful drug use. The research paper consistently examines regulations on their compliance with the fundamental categories of criminal law and the objectives of law enforcement activities. Conclusions are drawn about the inconsistency of certain provisions and solutions are determined. Based on the doctrinal provisions of criminal law and materials of judicial practice, proposals are formulated to improve the legislative description of the offenses that create conditions for illicit drug use.